The role of practicing the adapted promotional physical activity in developing the self- concept for deaf-mute juniors -A field study on "hearing-impaired children school" in M'sila - بلقاسم بن عبد الرحمان,; zouak amhamed, (sports creativity, 2025)
Objectives of the study:-highlight the role of practicing the adapted promotional physical activity in developing the self-concept for deaf-mute juniors. -Reveal the statistical differences in self-concept between practitioners and non-practitioners of recreational physical activity modified by the deaf. - Reveal the statistical differences in self-concept between practitioners of recreational physical activity modified by the deaf based on sex-affect. - Reveal the statistical differences in self-concept between practitioners of recreational physical activity modified by the deaf based an age-affect. - Method used in the study: descriptive approach -Society and Study Sample: The study population consists of deaf, while the sample of the study of deaf children in School of Hearing Impaired Children in "Msila" -Data and information collection tools: measure of the self-concept of the deaf. -Field application procedures: After having prepared the Scale، printed it and confirmed the statistical properties of the field research toolwe gave it to the children of the school of children with hearing loss. The state of "Msila" and with the help of a specialist in sign language. - Main results:-The adapted promotional physical activity has an important role in Enhancing and developing the self-concept among deaf-mute juniors. -There are some statistical differences of self-concept among the practitioners and non-practitioners of the adapted recreational physical activity by deaf-mute and for the practicing category. -There are statistically significant differences in self-concept among practitioners of leisure-relatedphysical activity of the deaf-mute based on sex-affect and for males. -There are statistically significant differences in self-concept of recreational physical activity practitioners adapted to deaf-mute based an age-affect and for elder category. -Suggestions: -Propose sports programs to develop -self-concept for people with disabilities. -Provide support and opportunities to centers that care for people with disabilities. -Contribution of all media to awareness of the problems of people with special needs and how to deal with them. -Encourage people with special needs to participate in sports activities.